Richard E. Wagner (Ed.): James M. Buchanan—A theorist of political economy and social philosophy - Karen Horn (Constitutional Political Economy, 2020)
Richard E. Wagner has published a multidisciplinary collection of fifty essays written by different scholars in the areas of James M. Buchanan's wide-ranging work. This volume is so broad in scope, so rich in fascinating reflections, so instructive that anybody should benefit from it who has a genuine, if critical, interest in Buchanan's work.
Keywords: 330; Political Science; Constitutional Law; Economic Theory/Quantitative Economics/Mathematical Methods